DASAR HUKUM PELAKSANAAN SYARIAT ISLAM DI BIDANG BISNIS DALAM TATA HUKUM INDONESIA - SYAHRANI SYAHRANI (Islamic Economics and Business Faculty of UIN Antasari, 2014)
The implementation of Islamic Sharia law in the business has had a legal basis in the Indonesian legal system. The legal basis is the Constitution of the Republic of Indonesia of 1945, especially article 29, some Laws and some Government Regulations, or other regulations which related to the developing sharia business, such as Law of the Republik Indonesia Number 7 Year 1992 in conjunction with Law Number 10 Year 1998 on the amendment of Law Number 7 Year 1992 on banking, Law Number 21 Year 2008 on Islamic Banking. The developing Financial Institution or Sharia Business, among other things, Islamic Banking, Islamic Insurance, Sharia investment fund shares, Sharia mortgage and others.